An Improved PWM Technique to Achieve Continuous Input Current in Common-Ground Transformerless Boost Inverter - Lee, Sze Sing; Siwakoti, Yam P.; Lim, Chee Shen; Lee, Kyo Beum (IEEE Transactions on Circuits and Systems II: Express Briefs, 2020)
A latest common-ground transformerless inverter for photovoltaic (PV) system has demonstrated its superiority over its existing counterpart due to its merits of single-stage structure and voltage boost capability. The exploited modulation scheme, however, led to discontinuous input current that draws high peak current from the source and causes high input power fluctuation in the converter. Such discontinuous and high peak current are detrimental to the PV source. Addressing this concern, this brief proposes a new modulation technique that achieves continuous input current with reduced peak magnitude while in the meantime ensures a good quality ac output voltage. Simulation and experimental results of a laboratory prototype are provided to verify the effectiveness of the proposed modulation technique.
Keywords: Continuous input; High input power; High-peak currents; Modulation schemes; Modulation techniques; Photovoltaic systems; Transformerless; Transformerless inverters; Common-ground; continuous input current; PWM technique; transformerless inverter; voltage-boosting